PENGARUH PRENATAL YOGA DAN AKUPRESURE TITIK BL67 (ZHIYIN) TERHADAP OPTIMALISASI POSISI JANIN PRIMIGRAVIDA USIA KEHAMILAN 36 MINGGU - Setiana Andarwulan; Encup (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2025)
Pregnancy is a very vulnerable period, not only for the pregnant woman but also for the safety of the fetus in the womb. Pregnancy is a physiological condition, but normal pregnancy can also turn into pathological pregnancy such as changes in the baby's position that are not optimal. In a natural effort to optimize the baby's position, prenatal yoga and BL 67 acupressure can be done. In this way, the mother and baby in labor can walk normally and naturally. This type of research uses quantitative research with a pre-test and post-test design. The total population used was 40 respondents with a research sample used of 39 respondents in accordance with the inclusion criteria. The number of samples was treated and observed using SOPs and assessment checklists. Next, the collected data was analyzed using the Wilcoxon signed test. With significance, if the calculated value is <0.05, then Ho is rejected and H1 is accepted. The results of the research show the influence of Prenatal Yoga and Acupressure Point BL67 (Zhiyin) on Optimizing the Position of the Primigravida Fetus in the Third Trimester of Pregnancy 36-42 Weeks at the Cerme Community Health Center with the Wilcoxon signed statistical test, the p value is 0.000 (< 0.05) so it can be concluded that Ho is rejected and H1 is accepted. Which means there is an influence of prenatal yoga and acupressure at the BL67 (Zhiyin) point on optimizing the position of the primigravida fetus in the third trimester of pregnancy 36-42 weeks at the Cerme Health Center. In this way, the research results can be implemented as well as possible.